Associations Between Sprint Mechanical Properties and Change of Direction Ability and Asymmetries in COD Speed Performance in Basketball and Volleyball Players - Zhihao Zhang; Mingchen Jiang; Yifan Jing; Mingjia Li; Yanchun Li; Xiaolin Yang (Life)
This study aimed to assess the associations between sprint force–velocity profile variables with change of direction (COD) performance and to investigate the impact of these variables on asymmetries in COD speed performance. Ninety-nine participants (volleyball players: n = 44, basketball players: n = 55) performed 40 m sprints for Fv relationship calculation, two COD tests (Modified Agility T-test and 505 test). A partial least squares (PLS) regression analysis was conducted to determine the relationships between the variables. The V0 was the most influential variable; it was negatively associated with COD performance variables (β = −0.260, −0.263 and −0.244 for MAT, 505-D and 505-ND, respectively), and F0 (β = 0.169, 0.163) was associated with the COD performance variables (COD deficit D and COD deficit ND, respectively), slightly larger than the effects of Fvslope (β = −0.162, −0.146), DRF (β = −0.159, −0.142) and Pmax (β = −0.162, −0.146). For COD deficit imbalance, the DRF (β = −0.070) was the most influential variable followed by Fvslope (β = −0.068), F0 (β = 0.046) and gender (β = 0.031). V0 and RFmax were the critical variables for improving COD performance that includes linear sprints, while DRF, Fvslope, F0 and Pmax collectively influence 180° COD performance. Meanwhile, DRF and Fvslope were important factors for asymmetries in COD speed performance. It is recommended to use the Fv profile to diagnose different COD movement patterns and then develop training plans accordingly for team sports played on smaller courts, such as basketball and volleyball.